2012
DOI: 10.1620/tjem.228.43
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the Glutathione-S-Transferase M3 Gene Promoter is Associated with Oxidative Stress in Acute-on-Chronic Hepatitis B Liver Failure

Abstract: Chronic hepatitis B (CHB) is a major cause for liver disease worldwide, ranking as the first cause for liver cirrhosis and hepatocellular carcinoma. Acute-on-chronic hepatitis B liver failure (ACHBLF) is most commonly caused by acute severe exacerbation during CHB virus infection. The pathophysiology of ACHBLF is still poorly understood. Glutathione-S-transferase (GST) M3 belongs to GSTs superfamily and it has been demonstrated to contribute to oxidative stress-mediated liver damage. The present study was aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Thus, lipid peroxidation products were introduced as potential candidates for disease progression and prognosis. Another study in which patients with acute or chronic hepatitis B whose plasma MDA levels were positively correlated with the MELD scores (r = 0.588) also supported these candidates (55). …”
Section: Resultsmentioning
confidence: 89%
“…Thus, lipid peroxidation products were introduced as potential candidates for disease progression and prognosis. Another study in which patients with acute or chronic hepatitis B whose plasma MDA levels were positively correlated with the MELD scores (r = 0.588) also supported these candidates (55). …”
Section: Resultsmentioning
confidence: 89%
“…CpG island hypermethylation of gene promoter can affect gene functions and inhibit protein expression by regulating and inactivating gene transcription [24,25]. For example, aberrant methylation of CpG island of the GSTM3 gene promoter is involved in oxidative injury upon liver failure [26]. Furthermore, CpG island methylation of the BRCA1 gene promoter is associated with breast cancer, and can therefore be used as a biological marker of breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…The modified DNA was amplified by MSP using primers specific for methylated and unmethylated GSTP1 and GSTM3. The primers sequences were the same with those in previous studies (Esteller et al 1998;Kollermann et al 2006;Li et al 2011a;Qi et al 2012). The MSP-amplified region of GSTP1 is from +78 to +168 within a CpG island in the 5′ region of GSTP1 gene.…”
Section: Sodium Bisulfite Modification and Methylation-specific Polymmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α) and malondialdehyde (MDA), markers for oxidative stress, are elevated in patients with HBV infection (Lara-Pezzi et al 1998a, b;Acar et al 2009;Tsai et al 2009). Our previous studies demonstrated that oxidative stress was associated with severity of HBV infection (Li et al 2011a;Qi et al 2012). Moreover, we found that glutathione-S-transferase P1 (GSTP1) and glutathione-S-transferase M3 (GSTM3) promoters were hypermethylated in acute-on-chronic hepatitis B liver failure, and the degree of methylation was associated with oxidative stress (Li et al 2011a;Qi et al 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation